ANÁLISE ESPAÇO-TEMPORAL DA TUBERCULOSE EM INDÍGENAS NO BRASIL. - FERREIRA, Thaís Furtado (2019)
INTRODUCTION: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and although it is curable, it is still a serious global public health problem. Among the natives, higher incidences of TB have been found more than in another race/color. OBJECTIVE: To analyze the spatial-temporal distribution of TB cases among indigenous people in Brazil. METHOD: This is an ecological study carried out with all new cases of TB in indigenous people reported in the period 2011-2017 in the Notification Disease Information System (SINAN) of the National Program for TB Control of the Ministry of Health. Data were collected in January 2019. For the study of temporal analysis, the incidences were calculated for each year in three units of analysis: Brazil, the regions and the Federative Units (FU), these being standardized by the direct method according to sex and age. The Prais-Winsten generalized linear regression model was used to evaluate the growth, decreasing or stable variations from the analysis of the growth measure and the level of significance (p <0.05). For the study of spatial analysis, the municipalities were used as unit of analysis being calculated the gross incidence and then the incidences adjusted by the local empirical Bayesian method. For the calculation, the average number of TB cases in indigenous people occurred in the municipality and, as denominator, the average indigenous population living in the respective municipality, multiplied by 100,000. The Moran Global and Local Indices were calculated to observe the existence of spatial autocorrelation of TB cases and to delimit high and low risk clusters. Statistical analyzes were performed in Stata® software version 14.0 and GeoDa version 1.10. All maps were built in QGIS 3.6.2 software. RESULTS: A total of 6,520 cases of TB were reported in indigenous communities, which 62.6% lived in rural areas. The average incidence of TB in indigenous people in Brazil was 109 / 100,000. In the analysis by region of the country, the highest incidence occurred in the Midwest, North and Southeast regions. In the UF analysis, the highest incidences were found in Mato Grosso, São Paulo, Rondônia, Mato Grosso do Sul, Acre, Maranhão, Pará and Rio de Janeiro. The trend of the disease in the natives was stable both in the country and in most of its regions and UF. TB was distributed in a heterogeneous way in the Brazilian municipalities, and this distribution did not happen randomly, with High Risk areas concentrated in the North and Central-West regions of the country and Low Risk in most states in the Northeast region and regions Southeast and South. CONCLUSION: TB disproportionately affects Brazilian natives and the present study, by identifying regions, UF and agglomerates at risk for TB in indigenous people in Brazil can contribute to the elaboration and strengthening of more specific control actions.